Annotation Text as Strategy to Teach Reading for General Communication - Astried Damayanti (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2020)
The researcher conducted the research based on teaching and learning Reading for General Communication. It was carried out for the first semester students of English Language Education Department of STKIP PGRI Trenggalek, consisting 50 students. The research was purposed to apply Annotation Text in teaching and learning reading. Annotating text means giving underline, highlight, symbolic notation or code of a text. It helps the students to give notes, key words of important information of a text. The research was also aimed to know the students’ reading comprehension after the annotation text applied and their response toward annotation text in learning reading. Summarization is used to evaluate the students’ comprehension of the text. The students were instructed to make a summary based on the text after annotating it. Attitude scale was utilized to know the students’ responses toward the use of Annotating Text in learning reading. The result of summarization showed that the mean of students’ work was 82.3 Meanwhile, the result of attitude scale indicates that the students gave good responses toward the application of Annotation Text in learning Reading for General Communication.